Synthesis of Evodileptin B, a Natural Anthranilate Derivative Isolated from Evodia lepta, and Evaluation of Its Therapeutic Potential against Parkinson's Disease. Issue 5 (29th March 2022) - Kim, Soobin; Yang, Wooin; Cha, Dong Seok; Han, Young Taek
Abstract: Evodileptin B (1 ) is a natural anthranilate derivative isolated from the ethanol extract of the aerial parts of Evodia lepta (Spreng.) Merr., a traditional medicinal plant of the family Rutaceae. We readily synthesized 1 via the amidation of phloretic with methyl anthranilate and evaluate its neuroprotective activity using a C. elegans Parkinson's disease (PD) model. The results showed that evodilpetin B ameliorated MPP + ‐induced dopaminergic (DA) neurodegeneration in a dose‐dependent manner. Evodileptin B treatment also significantly improved the DA neurotransmission‐related behavioral defects such as reduced locomotory and food‐sensing ability of worms under MPP + exposure conditions, suggesting its potential application for the functional restoration of DA neurons. In addition, we found that 1 has an ability to regulate aggregation of α‐synuclein by increasing proteasome activity in the human α‐synuclein‐expressing mutant worms. These results demonstrate that evodileptin B has strong neuroprotective properties and may be useful in the treatment of PD. Abstract :